Quantification of Brucella sp. In cattle in the province Canta, Lima - Huguet T., Carmen (2005)
The objective of this study was to determine the presence of Brucella sp. in cattle of the province of Canta, Lima, through the detection of antibodies in blood using the Rose Bengal test and then, the complement fixation test to confirm positive sera. A total of 486 serum samples were analysed and only one from the district of Santa Rosa de Quives was found positive. This indicated that the prevalence was 0.21% (1/486) with a confidence interval of 0.09 till 0.60%. The results showed that the presence of Brucella sp. in the province of Canta was very low, which may allow the implementation of a program for Brucella eradication.